Pengabdian Peningkatan Keterampilan Menyusun Penelitian Tindakan Kelas (PTK) bagi Guru-Guru di Aceh Timur - Jamali; Jamil, Muhammad; Muana Refi, Teuku; Wiriani, Erni; Aziz, Abdul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2021)
The purpose of this activity is to train teachers in East Aceh District so that they are able to understand why it is important to implement PTK and teachers can compile PTK reports using learning models. The method of implementing community service activities consists of classical and discussion which includes several stages, namely; 1) submission of systematic material for proposal writing, 2) material regarding, 3) technical implementation of research, 4) clinical preparation of PTK, 5) assistance for research implementation and 6) preparation of final research reports. Based on the results of the activity it can be seen; 1) PTK is very important for teachers to understand as professional development of teachers through three things, namely; research, write and develop the profession in a sustainable manner and include learning models that can affect student learning outcomes, 2) The implementation of training and mentoring for teachers in East Aceh District can have a direct impact on increasing knowledge about the preparation of PTK by using models learning, has provided technical knowledge for teachers in order to compile PTK reports, 3) Local government response is needed, especially the Education Office in carrying out similar activities so that participants who take part in these activities are fulfilled seeing that the number of teachers in East Aceh Regency is high, 4) partnership and cooperation between the Indonesian Academy of Banking Finance, East Aceh Regency and SDN East Aceh Regency.